The course of fight and the level of sports achievements in judo - Sterkowicz, S.; Lech, G.; Almansba, R. (Archives of Budo, 2007)
The purpose of this paper was to demonstrate differences in the fi ghting methods adopted by medallists during All-Polish Judo Competitions in relation to the competitors with a lower level of successes. Material/methods: The research material was a video recording during the Polish Judo Championships, which took place in Chorzów (Chorzów `98) and Wroclaw (Wroclaw `99). Each and every tournament fight (n = 518) was statistically analysed in order to defi ne the differences in the values of indices that characterise technical and tactical schooling. Results: In the recapitulation it was said that the level of the results achieved during the Polish Championships was mostly infl uenced by the activity of the contestants. Some signifi cant differences were also observed in terms of the effectiveness of particular technical actions and, to some extent, the level of achievements depended on the effectiveness of technical actions and the proportion of tactical actions. Conclusions: The information mentioned above should be taken into account by coaches when they plan and conduct schooling in their sports clubs.